Angiogenic potential of human mesenchymal stromal cell and circulating mononuclear cell cocultures is reflected in the expression profiles of proangiogenic factors leading to endothelial cell and pericyte differentiation. - Katriina Joensuu; Liina Uusitalo‐Kylmälä; Teuvo A. Hentunen; Terhi J. Heino (My University, 2025)
Endothelial progenitors found among the peripheral blood (PB) mononuclear cells (MNCs) are interesting cells for their angiogenic properties. Mesenchymal stromal cells (MSCs) in turn can produce proangiogenic factors as well as differentiate into mural pericytes, making MSCs and MNCs an attractive coculture setup for regenerative medicine. In this study, human bone marrow-derived MSCs and PB-derived MNCs were cocultured in basal or osteoblastic medium without exogenously supplied growth factors to demonstrate endothelial cell, pericyte and osteoblastic differentiation. The expression levels of various proangiogenic factors, as well as endothelial cell, pericyte and osteoblast markers in cocultures were determined by quantitative polymerase chain reaction. Immunocytochemistry for vascular endothelial growth factor receptor-1 and α-smooth muscle actin as well as staining for alkaline phosphatase were performed after 10 and 14 days. Messenger ribonucleic acid expression of endothelial cell markers was highly upregulated in both basal and osteoblastic conditions after 5 days of coculture, indicating an endothelial cell differentiation, which was supported by immunocytochemistry for vascular endothelial growth factor receptor-1. Stromal derived factor-1 and vascular endothelial growth factor were highly expressed in MSC-MNC coculture in basal medium but not in osteoblastic medium. On the contrary, the expression levels of bone morphogenetic protein-2 and angiopoietin-1 were significantly higher in osteoblastic medium. Pericyte markers were highly expressed in both cocultures after 5 days. In conclusion, it was demonstrated endothelial cell and pericyte differentiation in MSC-MNC cocultures both in basal and osteoblastic medium indicating a potential for neovascularization for tissue engineering applications.